A Study on Perceptions on Managers on corporate social responsibility (CSR) - Porkodi, T.; Venkatramaraju, D. (International Journal of Psychosocial Rehabilitation, 2020)
Creating a strong business and building a better world are not conflicting goals; they are both essential ingredients for long term- success.” – William Clay Corporate and markets are not created by God or nature, but by the business man. Intention of business must travel beyond the walls of the rigid corporate structure flowing into the lives of the needy and the anxious. In fact, it must contribute to the growth of the society since a business enterprise is a growth stimulator of society. “The purpose of business is to serve the society,” so said one of the successful business legends of India, J R D Tata. Business corporations are perhaps the most influential organizations in society and have long been recognized as important contributors to the common good. Society, grants corporations unique privileges in order to harness their great capacities to serve its needs. Today, companies realize their responsibility to serve the stakeholder and society to whom they owe their existence. Millions of people lack in basic amenities and dwell in poverty: a situation that cannot be resolved by the government alone, which is the only hope of the people. But one single hand can’t make a sound. That is an adequate reason, for concerted action on the part of powerful corporations, those who contribute to make the difference in society. For example, in the 1940’s, the founding father of Adithya Birla group of companies Shri G.D. Birla espoused the ‘Trusteeship’ concept of management. With that motive, they started to invest part of their profits beyond business, for the larger good of society.